Cyclohexane Rings Reduce Membrane Permeability to Small Ions in Archaea‐Inspired Tetraether Lipids. Issue 5 (23rd December 2015) - Koyanagi, Takaoki; Leriche, Geoffray; Onofrei, David; Holland, Gregory P.; Mayer, Michael; Yang, Jerry
Abstract: Extremophile archaeal organisms overcome problems of membrane permeability by producing lipids with structural elements that putatively improve membrane integrity compared to lipids from other life forms. Herein, we describe a series of lipids that mimic some key structural features of archaeal lipids, such as: 1) single tethering of lipid tails to create fully transmembrane tetraether lipids and 2) the incorporation of small rings into these tethered segments. We found that membranes formed from pure tetraether lipids leaked small ions at a rate that was about two orders of magnitude slower than common bilayer‐forming lipids. Incorporation of cyclopentane rings into the tetraether lipids did not affect membrane leakage, whereas a cyclohexane ring reduced leakage by an additional 40 %. These results show that mimicking certain structural features of natural archaeal lipids results in improved membrane integrity, which may help overcome limitations of many current lipid‐based technologies. Abstract : Extremophile Archaeal organisms thrive in harsh environments in part as a result of the unusual structural features present in their lipids. A systematic study of synthetic lipids reveals that membrane tethering and incorporation of cyclohexane rings into the tethered segment are two key structural features present in natural archaeal lipids that can improve membrane integrity by decreasing membrane permeability to small ions.